The Devil's Seeds. Duke, Lords and Rebel Communities (Canavese valleys, 1446-1450) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
In the late fourteenth century rural communities of northern Piedmont (a territory called Canavese) rose up against their lords in a vast insurrection known as Tuchinaggio (1386-1391). Despite the fact that the count of Savoy suppressed the revolt, rebellions started again and went on until the mid-sixteenth century, involving other rural lordships, but concentrating in the alpine valleys. In the context of this new wave of rebellion, the essay scrutinizes the large riot occurred between 1446 and 1450, by analysing the perspectives and the objectives of the various political actors involved: valley communities, the duke of Savoy, local lords. Revolts are examined as the expression of the communities’ political projects, rather than as a mere response to oppression by the lords: communities sought to be admitted under the direct jurisdiction of the duke, thus breaking free from the lords’ mediating role.
Keywords: Revolts; rural communities; Alps; rural lordship; Duchy of Savoy